HOW ISLAMIC FINANCIAL LITERACY SHAPES CUSTOMER ATTITUDE, SUBJECTIVE NORM, AND PERCEIVED BEHAVIORAL CONTROL IN USING ISLAMIC BANKS IN INDONESIA - Safitri, Rini; Wuryaningsih, Wuryaningsih; Amrullah, Abdul Malik Karim; Novianti, Khusnul Rofida (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2025)
This study aims to examine the influence of Islamic financial literacy, attitude, subjective norms, and perceived behavioral control on the intention to use Islamic banks in Indonesia. Specifically, this study investigates the indirect effect of Islamic financial literacy on the intention to use Islamic banks through attitude, subjective norms, and perceived behavioral control. Data were obtained through a survey of 572 students from Islamic Higher Education Institutions in Indonesia and processed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that Islamic financial literacy significantly influences attitudes, subjective norms, and perceived behavioral control regarding Islamic banking services. Subsequently, these factors (attitude, subjective norm, and perceived behavioral control) were proven to be strong predictors of an individual's intention to use Islamic banks. These findings validate the Theory of Planned Behavior (TPB) in Islamic banking, showing that Islamic financial literacy is a key factor influencing TPB. This study highlights the importance of financial literacy education in increasing the adoption of Islamic banking services. By promoting Islamic financial literacy within university programs, future graduates will have a deeper understanding of Islamic banking principles (such as the prohibition of riba, risk-sharing, and asset-backed financing). This awareness will enhance the likelihood of choosing Islamic banking services and advocating them within society.